2000
DOI: 10.1016/s0168-6496(00)00021-0
|View full text |Cite
|
Sign up to set email alerts
|

Mathematical estimations of hyper-ammonia producing ruminal bacteria and evidence for bacterial antagonism that decreases ruminal ammonia production

Abstract: Mixed ruminal bacteria (MRB) from cattle fed hay produced ammonia from protein hydrolysate twice as fast as MRB from cattle fed mostly grain, and a mathematical model indicated that cattle fed hay had approximately four-fold more hyper ammonia-producing ruminal bacteria (HAB). HAB had a high maximum velocity of ammonia production (V max ) and low substrate affinity (high K m ), but simulations indicated that only large changes in V max or K m would cause a large deviation in HAB numbers. Some carbohydrate-ferm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
19
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 28 publications
0
19
0
Order By: Relevance
“…Different bacterial species can break down dietary protein and ferment peptides and amino acids with the concomitant production of ammonia and VFAs, but the rate of ammonia and ATP production can vary considerably (Rychlik and Russell, 2000). In our study, only modest changes in deamination activity were observed during the Figure 3 Analysis of principal components to evaluate the effect of casein supplementation on ruminal parameters.…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…Different bacterial species can break down dietary protein and ferment peptides and amino acids with the concomitant production of ammonia and VFAs, but the rate of ammonia and ATP production can vary considerably (Rychlik and Russell, 2000). In our study, only modest changes in deamination activity were observed during the Figure 3 Analysis of principal components to evaluate the effect of casein supplementation on ruminal parameters.…”
Section: Discussionmentioning
confidence: 65%
“…This result is consistent with the idea that greater availability of degradable protein will increase amino acid degradation by a more specialized population of ruminal bacteria. It has been estimated that hyper-ammonia producing bacteria have a lower substrate affinity (K m ) than the mixed ruminal bacteria, but the V max of ammonia production is ∼12.5-fold greater than the mixed ruminal bacteria of forage fed animals (Rychlik and Russell, 2000). Therefore, a higher RDP content in the diet could impact both SAD and the concentration of ruminal ammonia, demonstrating the influence of the diet in the activity of rumen microorganisms and nitrogen metabolism in the rumen (Bach et al, 2005;Calsamiglia et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Coculture experiments with HAB found that washed mixed-rumen bacteria (MRB) from cattle fed grain were able to decrease ammonia production from HAB, but MRB from cattle fed hay did not affect HAB (Rychlik and Russell, 2000). Those authors used autoclaved MRB and did not observe HAB inhibition.…”
mentioning
confidence: 99%
“…Previous work indicated that cattle fed hay had obligate amino acid-fermenting ruminal bacteria (1,6,17,24), and a mathematical model based on kinetic parameters indicated that these bacteria should account for approximately 5% of the total population (25). However, if ruminal fluid from a cow fed the same type of hay was serially diluted into basal medium supplemented with amino acids and peptides, little growth and ammonia production were detected in dilutions of Ն10 Ϫ6 (Fig.…”
Section: Discussionmentioning
confidence: 95%